2022
DOI: 10.1212/nxi.0000000000200027
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Reconstitution After Autologous Hematopoietic Stem Cell Transplantation in Multiple Sclerosis

Abstract: Background and ObjectivesAutologous hematopoietic stem cell transplantation (aHSCT) is increasingly used to treat aggressive forms of multiple sclerosis (MS). This procedure is believed to result in an immune reset and restoration of a self-tolerant immune system. Immune reconstitution has been extensively studied for T cells, but only to a limited extent for B cells. As increasing evidence suggests an important role of B cells in MS pathogenesis, we sought here to better understand reconstitution and the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The London study group demonstrated detectable viraemia in 80% of PwMS between day 23 and 46 post‐AHSCT 55 . A Swiss study identified viraemia in 2 of 20 PwMS undergoing AHSCT for MS; however, 90% of the cohort had been treated with B cell therapy prior to transplant, which may have contributed to the low rate of post‐transplant viraemia 56 . EBV DNAemia is common in patients treated with Alemtuzumab as a conditioning agent during allogenic HSCT 57 .…”
Section: How Ms Therapies Inform the Ebv Debatementioning
confidence: 99%
See 1 more Smart Citation
“…The London study group demonstrated detectable viraemia in 80% of PwMS between day 23 and 46 post‐AHSCT 55 . A Swiss study identified viraemia in 2 of 20 PwMS undergoing AHSCT for MS; however, 90% of the cohort had been treated with B cell therapy prior to transplant, which may have contributed to the low rate of post‐transplant viraemia 56 . EBV DNAemia is common in patients treated with Alemtuzumab as a conditioning agent during allogenic HSCT 57 .…”
Section: How Ms Therapies Inform the Ebv Debatementioning
confidence: 99%
“… 55 A Swiss study identified viraemia in 2 of 20 PwMS undergoing AHSCT for MS; however, 90% of the cohort had been treated with B cell therapy prior to transplant, which may have contributed to the low rate of post‐transplant viraemia. 56 EBV DNAemia is common in patients treated with Alemtuzumab as a conditioning agent during allogenic HSCT. 57 No data are available for treatment with Alemtuzumab alone, or with Cladribine.…”
Section: How Ms Therapies Inform the Ebv Debatementioning
confidence: 99%
“…In another recent study, longitudinal multidimensional cytometry and immunoglobulin heavy chain (IgH) repertoire sequencing were used to investigate the B cell immune reconstitution in 20 MS patients receiving AHSCT with BEAM-ATG regimen and anti-CD20 treatment before and 1, 3, 6 and 12 months after AHSCT and compared to HC [ 10 •]. B-lymphocyte number recovered at 3 months and remained increased at 1 year post AHSCT.…”
Section: Mechanism Of Action and Biomarkersmentioning
confidence: 99%
“…The application of aHSCT involves mobilisation of haematopoietic stem cells (HSCs) and their progenitor cells, and ablation of lymphocytes using chemotherapy including cyclophosphamide and granulocyte colony stimulating factor. HSCs are harvested and subsequently reinfused, leading to reconstitution of the immune system and (in responders) suppression of MS relapses [ 24 , 86 ].…”
Section: A Note On Autologous Haematopoietic Stem Cell Transplantatio...mentioning
confidence: 99%